The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1093/qjmed/hcm134
|View full text |Cite
|
Sign up to set email alerts
|

New results from the Modification of Diet in Renal Disease study: the importance of clinical outcomes in test strategies for early chronic kidney disease

Abstract: A formula derived from the Modification of Diet in Renal Disease (MDRD) study in chronic renal disease is widely used to estimate glomerular filtration rate (GFR). Recently a ten-year follow-up of MDRD participants evaluated four tests of kidney function measured at baseline as predictors of important long-term clinical outcomes. Surprisingly, neither formula-estimated GFR nor reference method GFR showed a clear advantage over simple creatinine measurement whereas another test, cystatin C, looked more promisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…However, the use of eGFR to test patients without previously recognized CKD is not only controversial, but maybe ill-advised (13).…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of eGFR to test patients without previously recognized CKD is not only controversial, but maybe ill-advised (13).…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent studies have suggested that the MDRD calculated eGFR was no better than serum creatinine concentration alone in ‘diagnosing’ CKD, using the current KDOQI criteria [25, 26]. The necessity for repeated measurement to confirm the ‘chronicity’ of the decline in eGFR or the persistence of the manifestations of kidney damage imposes a severe limitation upon cross-sectional epidemiological studies.…”
Section: How Accurate Is the Kdoqi Classification In Identifying Ckd?mentioning
confidence: 99%
“…1,6 Knowledge of eGFR could also aid the selection of safe and effective dosing regimens for potentially toxic drugs that are eliminated largely by glomerular filtration, although the superiority of the MDRD-estimated eGFR over other estimates for this purpose is not well established. 7 Undoubtedly, the concept of eGFR has raised the profile of CKD in the community at large.…”
mentioning
confidence: 99%